Cretaceous fossil Raninoida De Haan, 1839 (Crustacea, Decapoda, Brachyura) from northeast Texas. (17th October 2016) - Franţescu, Ovidiu D.; Feldmann, Rodney M.; Schweitzer, Carrie E.
Abstract: Two new Raninoida crabs from the Cretaceous of Texas are described, Planocorystes robreidi new genus new species, and Texicancer new genus to accommodate Necrocarcinus renfroae . All the previously described raninoid-like decapods from the Pawpaw Formation have been reassigned according to Karasawa et al. (2014). Cretaceous raninoid-like crabs are the dominant taxa amongst the fossil decapods found in the Fort Worth, Texas, area, with hundreds of specimens collected. All of these fossils have been collected from limonitic nodules, and most of them present a good degree of preservation, with articulated pereiopods, pleons, venter and in rare occasions even the gills. The decapod fauna of the Pawpaw Formation represents a diverse population, with a large number of taxa in high abundance. One specimen of P . robreidi appears to exhibit a lethal bite mark.